Studi Peristiwa Pengumuman Kerjasama Interkoneksi ATM Bank Mandiri dan BCA (16 Januari 2012) Terhadap Kinerja Harga Saham Bank Mandiri dan BCA - , Meydia ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Information is a primary need for the capital marketâs investors. The cooperation announcement for ATM interconnection between Bank Mandiri and BCA is a âbig historyâ for the banking sector in Indonesia. This event, which has relevant information contents for investors, will cause market reactions and will be reflected by changes in stock prices. The aim of this research is to analyze the impact of cooperation announcement for ATM interconnection between Bank Mandiri and BCA (16 January 2012) on stock price reaction for Bank Mandiri and BCA. This research explored the issue by applying event study methodology for analyzing the market reaction, which is reflected by abnormal return with event window 10 days before, event date, and 10 days after the date of event. This research uses secondary data. The data is collected from Indonesia Stock Exchange. The data of this research consists of Bank Mandiriâs daily closing stock price, BCAâs daily closing stock price and Composite Stock Price Index (IHSG). Expected return in this research using Single Index Market Model. The results show that: (1) The cooperation announcement event for ATM interconnection between Bank Mandiri and BCA possess information content which makes stock market to react, itâs reflected by significant abnormal return around the event. (2) The abnormal return that is reflected around the event, shows that there is a leakage of information before the event announced to the public. It means that from this event study we know that Bank Mandiri receives more abnormal return due to it has more ATMs compare to BCA.